Effect of zinc plating of low carbon steel on corrosion resistance in cassava fluid environment (2008)
This research work investigated the corrosion resistance of zinc plated low carbon steel in cassava fluid (i.e. containing hydrogen cyanide). It simulated the effect of continuous use of the material in a cyanide environment where corrosion products are left in place. Low carbon steel samples were zinc electroplated at voltages between 0˙5 and 0˙9 V for 5 to 20 min. The plated samples were then subjected to a cassava fluid environment for 30 days. The electrode potentials, in mV (SCE), were measured every day. Weight loss was determined at intervals of 5 days for duration of the exposure period. The result showed corrosion attack on the zinc plated steel, the severity increasing with increasing weight of zinc coating on substrate. The result showed that thinly plated low carbon steel did not have any advantage over unplated steel and were quickly stripped of their zinc plating with resultant corrosion of the underlying steel substrate. Heavily zinc plating steel was observed to offer some protection for the steel but not for a long time. The pH of the cassava solution which initially was acidic because of the cyanide content in the cassava was observed to progress to neutrality after 5 days and then became slightly alkaline at the end of the 30 days test (because of corrosion product contamination of the cyanide), contributing to the reduced corrosion rate. Unplated steel was found to be unsuitable for the fabrication of cassava processing machinery without some form of surface treatment, but unfortunately, zinc is not suitable as a protective coating in this environment.